Whole-Body Vibration Training on Oxidative Stress Markers, Irisin Levels, and Body Composition in Women with Fibromyalgia: A Randomized Controlled Trial - dos Santos, Jousielle Márcia; Taiar, Redha; Ribeiro, Vanessa Gonçalves César; da Silva Lage, Vanessa Kelly; Scheidt Figueiredo, Pedro Henrique; Costa, Henrique Silveira; Pereira Lima, Vanessa; Sañudo, Borja; Bernardo-Filho, Mário; Sá-Caputo, Danúbia da Cunha de; Dias Peixoto, Marco Fabrício; Mendonça, Vanessa Amaral; et al. (Bioengineering, 2023)
(1) Background: Mitochondrial dysfunction and redox imbalance seem to be involved in fibromyalgia (FM) pathogenesis. The results of our previous studies suggest that whole-body vibration training (WBVT) would improve redox status markers, increase blood irisin levels, and ameliorate the body composition of women with FM. (2) Objective: The current study aimed to investigate WBVT on oxidative stress markers, plasma irisin levels, and body composition in women with FM. (3) Methods: Forty women with FM were randomized into WBVT or untrained (UN) groups. Before and after 6 weeks of WBVT, body composition was assessed by dual-energy radiological absorptiometry (DXA), and inflammatory marker activities were measured by enzymatic assay. (4) Results: Body composition, blood irisin levels, and oxidative stress markers were similar between UN and WBVT groups before the intervention. After 6 weeks of intervention, the WBVT group presented higher irisin levels (WBVT: 316.98 ± 109.24 mg·dL³, WBVT: 477.61 ± 267.92 mg·dL³, p = 0.01) and lower TBARS levels (UN: 0.39 ± 0.02 nmol MDA/mg protein, WBVT: 0.24 ± 0.06 nmol MDA/mg protein, p = 0.001) and visceral adipose tissue mass (UN: 1.37 ± 0.49 kg, WBVT: 0.69 ± 0.54 kg, p = 0.001) compared to the UN group. (5) Conclusions: Six weeks of WBVT improves blood redox status markers, increases irisin levels, and reduces visceral adipose tissue mass, favoring less cell damage and more outstanding oxidative balance in women with FM.
Number: 2
Keywords: chronic condition; fibromyalgia; muscle pain; obesity; oxidative stress; visceral adipose tissue; whole-body vibration